Model‐based constraints on the lunar exosphere derived from ARTEMIS pickup ion observations in the terrestrial magnetotail. Issue 5 (30th May 2013) - Poppe, A. R.; Halekas, J. S.; Samad, R.; Sarantos, M.; Delory, G. T.
Abstract : [1] We use Acceleration, Reconnection, Turbulence and Electrodynamics of the Moon's Interaction with the Sun (ARTEMIS) measurements of lunar exospheric pickup ions in the terrestrial magnetotail lobes combined with a particle‐tracing model to constrain the source species and distributions of the lunar neutral exosphere. These pickup ions, generated by photoionization of neutral species while the Moon is in the magnetotail lobes, undergo acceleration from both the magnetotail convection electric field and the lunar surface photoelectric field, giving rise to distinct pickup ion flux, pitch angle, and energy distributions. By simulating the behavior of lunar pickup ions in the magnetotail lobes and the response of the twin ARTEMIS probes under various ambient conditions, we can constrain several physical quantities associated with these observations, including the source ion production rate and the magnetotail convection velocity (and hence, electric field). Using the model‐derived source ion production rate and established photoionization rates, we present upper limits on the density of several species potentially in the lunar exosphere. In certain cases, these limits are lower than those previously reported. We also present evidence that the lunar exosphere is displaced toward the lunar dawnside while in the terrestrial magnetotail based on fits to the observed pickup ion distributions. Key Points: We present a model of pick‐up ion fluxes at the Moon in the Earth's magnetotail We use the model to fit ARTEMIS lunar pick‐up ion observations in the m'tail We improve constraints on lunar exospheric neutral densities and distributions